Design and Simulation of a Triple Absorber Layer Perovskite Solar Cell for High Conversion Efficiency - Yousfi, Abderrahim; Saidani, Okba; Messai, Zitouni; Zouache, Rafik; Meddah, Mohamed; Belgoumri, Younes (East European Journal of Physics, 2023)
This paper presents a comprehensive simulation study on the influence of a triple absorber layer configuration in a perovskite-based solar cell using the SCAPS-1D software, under AM1.5 illumination. The simulated structure comprises a Cesium Tin-Germanium Triiodide (CsSn0.5Ge0.5I3) absorber layer sandwiched between Indium gallium zinc oxide (IGZO) and Cu2O layers. The main objective of this study is to enhance the power conversion efficiency (PCE) by optimizing the thicknesses of each layer. To validate our simulation results, we compare them with experimental data obtained from existing literature, and we observe a satisfactory agreement between the two. Our findings reveal that the maximum PCE of 28% can be achieved by utilizing specific thickness values for each layer. Specifically, the optimal thicknesses are determined to be 20 nm for the IGZO layer, 200 nm for the Cu2O layer, and 700 nm for the perovskite layer. These optimized thickness values lead to a significant improvement in the PCE of the solar cell, reaching 29%. This achievement highlights the effectiveness of our proposed triple absorber layer configuration and demonstrates its potential to enhance the overall performance of the perovskite-based solar cell. Overall, this study provides valuable insights into the optimization of the absorber layer configuration in perovskite solar cells, leading to improved power conversion efficiency.